Mechanisms for rescue of corpus luteum during pregnancy: gene expression in bovine corpus luteum following intrauterine pulses of prostaglandins E-1 and F-2 alpha - Ochoa, Julian C. [UNESP]; Penagaricano, Francisco; Baez, Giovanni M.; Melo, Leonardo F.; Motta, Jessica C. L.; Garcia-Guerra, Alvaro; Meidan, Rina; Pinheiro Ferreira, Joao C. [UNESP]; Sartori, Roberto; Wiltbank, Milo C. (Oxford Univ Press Inc, 2018)
In ruminants, uterine pulses of prostaglandin (PG) F-2 alpha characterize luteolysis, while increased PGE(2)/PGE(1) distinguish early pregnancy. This study evaluated intrauterine (IU) infusions of PGF(2 alpha) and PGE(1) pulses on corpus luteum (CL) function and gene expression. Cows on day 10 of estrous cycle received 4 IU infusions (every 6 h; n = 5/treatment) of saline, PGE(1) (2 mg PGE(1)), PGF(2 alpha) (0.25 mg PGF(2 alpha)), or PGE(1) + PGF(2 alpha). A luteal biopsy was collected at 30 min after third infusion for determination of gene expression by RNA-Seq. As expected, IU pulses of PGF(2 alpha) decreased (P < 0.01) P4 luteal volume. However, there were no differences in circulating P4 or luteal volume between saline, PGE(1), and PGE(1) + PGF(2 alpha), indicating inhibition of PGF(2 alpha)-induced luteolysis by IU pulses of PGE(1). After third pulse of PGF(2 alpha), luteal expression of 955 genes were altered (false discovery rate [FDR] < 0.01), representing both typical and novel luteolytic transcriptomic changes. Surprisingly, after third pulse of PGE(1) or PGE(1) + PGF(2 alpha), there were no significant changes in luteal gene expression (FDR > 0.10) compared to saline cows. Increased circulating concentrations of the metabolite of PGF(2 alpha) (PGFM; after PGF(2 alpha) and PGE(1) + PGF(2 alpha)) and the metabolite PGE (PGEM; after PGE(1) and PGE(1) + PGF(2 alpha)) demonstrated that PGF(2 alpha) and PGE(1) are entering bloodstream after IU infusions. Thus, IU pulses of PGF(2 alpha) and PGE(1) allow determination of changes in luteal gene expression that could be relevant to understanding luteolysis and pregnancy. Unexpectedly, by third pulse of PGE(1), there is complete blockade of either PGF(2 alpha) transport to the CL or PGF(2 alpha) action by PGE(1) resulting in complete inhibition of transcriptomic changes following IU PGF(2 alpha) pulses. Summary Sentence Treatment with PGF(2 alpha) induced dramatic changes in expression of 955 genes, based on RNA-Seq after the third PGF(2 alpha) pulse (FDR < 0.01), whereas simultaneous treatment with pulses of PGE(1) blocked luteolysis and gene expression induced by PGF(2 alpha).
Keywords: corpus luteum; luteolysis; prostaglandin F-2 alpha; prostaglandin E-1